2015
DOI: 10.1016/j.comgeo.2015.07.003
|View full text |Cite
|
Sign up to set email alerts
|

Higher-order triangular-distance Delaunay graphs: Graph-theoretical properties

Abstract: We consider an extension of the triangular-distance Delaunay graphs (TD-Delaunay) on a set P of points in the plane. In TD-Delaunay, the convex distance is defined by a fixed-oriented equilateral triangle , and there is an edge between two points in P if and only if there is an empty homothet of having the two points on its boundary. We consider higher-order triangular-distance Delaunay graphs, namely k-TD, which contains an edge between two points if the interior of the homothet of having the two points on it… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
13
0

Year Published

2018
2018
2021
2021

Publication Types

Select...
3
2
1

Relationship

2
4

Authors

Journals

citations
Cited by 8 publications
(13 citation statements)
references
References 20 publications
0
13
0
Order By: Relevance
“…The problem of computing a maximum matching in G S (P ) is one of the fundamental problems in computational geometry and graph theory [1,2,3,5,6,7,11]. Dillencourt [11] andÁbrego et al [1] considered the problem of matching points with disks.…”
Section: Previous Workmentioning
confidence: 99%
See 1 more Smart Citation
“…The problem of computing a maximum matching in G S (P ) is one of the fundamental problems in computational geometry and graph theory [1,2,3,5,6,7,11]. Dillencourt [11] andÁbrego et al [1] considered the problem of matching points with disks.…”
Section: Previous Workmentioning
confidence: 99%
“…Lemma 7 (Biniaz et al [7]). Let t 1 be a downward triangle which intersects a downward triangle t 2 through t 2 (s 1 ), and let a horizontal line intersects both t 1 and t 2 .…”
Section: Strong Matching In G (P )mentioning
confidence: 99%
“…See the following subsection for further background. Biniaz et al [12] proved that for any point set of size n, G (P ) has a strong matching of at least n−1 9 edges and G (P ) has a strong matching of at least (n − 1)/4 edges. We prove an upper bound on the size of a strong matching in Θ 6 -graphs by giving an example where the maximum strong matching in G (P ) has 2n/5 edges.…”
Section: Introductionmentioning
confidence: 99%
“…They also give lower bounds of (n − 1)/8 and n/5 , respectively. The lower bound for squares was improved to (n − 1)/4 by Biniaz et al [12] who also proved lower bounds of (n − 1)/9 for G and (n − 1)/4 for G .…”
Section: Introductionmentioning
confidence: 99%
“…This implies that there exist triangle-DG graphs that do not contain Hamiltonian paths or cycles. Biniaz et al [21] showed that 7-DG △ contains a bottleneck Hamiltonian cycle and that there exist points sets where 5-DG △ does not contain a bottleneck Hamiltonian cycle. Ábrego et al [3] showed that the DG □ admits a Hamiltonian path, while Saumell [92] showed that the DG □ is not necessarily 1-tough, and Our contributions.…”
Section: Convex Shape Delaunay Graphs and Hamiltonicitymentioning
confidence: 99%